Sarcopenia in geriatric psychiatry: feasibility of the diagnostic process and estimation of prevalence within a hospital context. Issue 5 (21st June 2021) - Sperlich, Esther; Fleiner, Tim; Zijlstra, Wiebren; Haussermann, Peter; Morat, Tobias
Abstract: Background: Sarcopenia is an age‐related progressive and general skeletal muscle disease associated with negative consequences such as falls, disability, and mortality. An early‐stage diagnosis is important to enable adequate treatment, especially in geriatric psychiatry. However, there presently is little information about the feasibility of diagnostic procedures and the prevalence of sarcopenia in clinical geriatric psychiatry settings. The aim of this study is to implement a diagnostic process for sarcopenia in a geriatric psychiatry hospital, to investigate its feasibility and to analyse the prevalence rates. Methods: A single‐centre cross‐sectional study over 3 months was conducted in a geriatric psychiatry hospital. All admitted patients with a diagnosis of dementia, depression, or delirium were screened regarding the clinical impression of frailty and sarcopenia according to the current diagnostic algorithm of the European Working Group on Sarcopenia in Older People 2 (EWGSOP2). Results: We found that short physical performance tests, such as the handgrip strength testing (91%) or 4 m walking test (91%), were applicable in our sample. The original standardized instructions of longer tests could not be performed appropriately, for example, in the five‐times‐sit‐to‐stand‐test (32%), the timed‐up‐and‐go‐test (68%), and the 400 m walking test (38%). Muscle mass measurements using bioelectric impedance analysis were feasible in all patients (100%). The analysis revealed an estimated prevalence rate for sarcopenia of 65% for patients suffering from dementia and 36% for patients suffering from depression. In our final analysis, 15 patients suffering from dementia, 19 suffering from depression, and no patient suffering from delirium were included [22 female (64.7%) and twelve male (35.3%) patients]. The patients were on average 78.9 ± 7.7 years old, with the youngest patient being 61 years old and the oldest patient 93 years old. Out of the total sample, 14 patients suffering from dementia and eight patients suffering from depression were diagnosed with a severe stage of sarcopenia. Conclusions: The EWGSOP2 algorithm seems to be applicable in the clinical routine of a geriatric psychiatry hospital. The high estimated prevalence rates of sarcopenia highlight the need for an early and comprehensive screening for sarcopenia in geriatric psychiatry.